Farmacodinamia de los antidepresivos inhibidores de la recaptación de serotonina en el trastorno depresivo mayor (2021)
Depression has become a major public health problem in recent years. Among the solutions proposed to treat it is drug therapy with antidepressants. Although they have made it possible to understand part of the neurochemical and molecular mechanisms behind the pathophysiology of depression, antidepressant do not represent an effective treatment for all patients, which could be related to the emphasis that has been given to solving depression caused by stress. In other words, therapy with frequently used antidepressants, such as Specific Serotonin Reuptake Inhibitors (SSRIs), focuses on reducing neuronal damage caused by stress, which is considered a risk factor for suffering from mood disorders. These attenuation is associated with the effects that antidepressant produce on some serotonin receptors, such as sensitization of 5HT1A heterreceptors and desensitization of 5HT1A autoreceptors and 5HT2A heteroreceptors...